The Effect of Academic Service Quality on the Image of State Universities Towards World Class University (Study of Foreign Students at Brawijaya University) - Tutik Andayani; Bambang Santoso Haryono; Lely Indah Mindarty (Wacana Journal of Social and Humanity Studies, 2020)
This research was conducted to analyze the effect of perceived service quality (expected service) and perceived service quality on perceived service quality and to determine the effect of perceived service quality on the image of state universities. This research is classified as explanatory research by using a quantitative descriptive approach. Structural Equation Modeling (SEM) research design with PLS (Partial Least Square) approach. The sampling method used is the nonprobability sampling method (purposive sampling). The number of samples was determined using the Yamane formula (Riduan and Kuncoro, 2008) and obtained as many as 50 foreign students. This study uses primary data collected with an instrument in the form of a questionnaire with a Likert scale. The analysis shows that the expected service variable (X1) shows a negative influence (-0.555) and is significant (t 4.755> 1.96) on the perceived service quality variable (service quality / Y1). In addition, perceived service (X2) variable perceived service quality (service quality / Y1) showed a positive influence (0.822) and significant (t 12,592> 1.96), whereas perceived service quality (service quality / Y1) with variable state image / Y2) shows a negative influence (-0.309) and significant (t 2,080> 1.96). It can be concluded that the perceived service quality and image of a tertiary institution is strongly influenced by whether or not the quality of service expected (expected service), as well as the service, received (perceived service) by foreign students.